2019
DOI: 10.1080/20421338.2019.1633096
|View full text |Cite
|
Sign up to set email alerts
|

Customers' loyalty to tablet commerce in Nigeria

Abstract: A visit to a traditional or online retailer with the wide variety of electronic devices -desktops, laptops, tablets, and smartphones, clearly, each device is capable of e-commerce activity and a device will be adopted according to a consumer's perceptions of value. Given the importance of human, cultural and personal values, this study purposefully selected Nigerian tablet consumers to better understand the factors that impact on the adoption of mobile commerce and tablet commerce in a developing economy. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 115 publications
3
7
0
Order By: Relevance
“…In the quantitative section, the reliability and construct validity of the measuring items were tested. The values of composite reliability and average variance extracted (AVE) were greater than 0.7 and 0.5, respectively for convergent validity which is tandem with Olaleye et al (2020a) and Olaleye, Sanusi, and Salo (2020b). Both descriptive and inferential statistics were utilized which include frequency, percentages, mean, standard deviation (SD) and t-test.…”
Section: Discussionmentioning
confidence: 99%
“…In the quantitative section, the reliability and construct validity of the measuring items were tested. The values of composite reliability and average variance extracted (AVE) were greater than 0.7 and 0.5, respectively for convergent validity which is tandem with Olaleye et al (2020a) and Olaleye, Sanusi, and Salo (2020b). Both descriptive and inferential statistics were utilized which include frequency, percentages, mean, standard deviation (SD) and t-test.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, [18] also highlighted the importance of trust in online shopping in Nigeria. Their work on u-commerce (ubiquitouscommerce) involving online shoppers in Nigeria, revealed that trust was pivotal in increased user perception and experience, noting that usability and privacy directly impact users' experiences.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Consumers like and will visit shopping websites with a simple and accessible user interface, which leads to satisfaction and increase in online repurchase intention (Rehman et al, 2019). A previous study has found that a system that is easy to use will be more widely accepted than those that are not (Olaleye et al, 2020).…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…However, empirical examinations of this issue revealed inconsistent results. For example, some scholars (Kahar et al, 2019) failed to find evidence that perceived ease of use influences repurchase intention, but other scholars (Olaleye et al, 2020;Trivedi & Yadav, 2020;Purani et al, 2019;Ozturk et al, 2016) found that this factor significantly influences repurchase intention. A similar issue was found in an empirical study on shopping experience, where several researchers (Quan et al, 2020) failed to find evidence that shopping experience influences repurchase intention, but other scholars (Japutra et al, 2021;Cachero-Martínez & Vázquez-Casielles, 2021;Jafarpour et al, 2017;Bilgihan, 2016) found that this factor significantly influences Repurchase Intention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation